(untitled) (American Journal of Islam and Society, 2004)
Abdessalam Yassine, a Moroccan Qur’anic scholar, passionately argues that Muslims need to return to the Qur’anic revelation and the prophetic method of Prophet Muhammad (pbuh) in order to resurrect the Muslim mind and worldview, which are currently subjugated to secular western thought. According to Yassine, the book’s purpose “is the establishment and reminding of the Prophetic Method” (p. 25). This argument is made in the format of an introduction and 37 subject variants (ranging in length from a few paragraphs to seven pages). Yassine juxtaposes the Muslim mind with that of the secular materialistic western mind, where the latter is shown to be deficient while the former, based on and nourished by revelation and the Sunnah, is considered to be truly emancipatory. He states: “When discussing the choice between two minds and two mentalities we have only two options: Either the sovereignty of the Revelation, pure and simple … Or the sovereignty of the arena, which occupied the other mind with its materialism, racialism and vagueness of its goals” (p. 9). Throughout the book, Yassine provides some insights into Islamic spiritual practice and critiques mainstream western thought. Interestingly, his essay “Ritual Purity” eloquently points out the importance of situating the body in Islamic spirituality and how its purification is interconnected with inner spiritual growth. In addition, he does not romanticize the current Muslim ummah and shift all blame to the West; rather, he critiques the ummah for being coopted by western materialism. However, I had numerous problems with this book, beginning with its premise. In an age of pluralistic societies, it is very hard to digest a discussion where one does not acknowledge that a pure “western mind” or a “Muslim mind” does not exist, because this assumption fails to acknowledge the difference and diversity among interpretations of text and ideas. Yassine employs the dominant discourses in both western and Islamic thought in order to forward his argument, which, in turn, leads to essentialism. Knowledge production is dynamic, and constructing such a binary framework perpetuates the idea that knowledge is static and fixed to a certain context, which only bolsters stereotypes ...